The Natural Rodenticidal Effect of Papain Papaya (Carica papaya L.) in Histopathological Changes of Albino Mice Organs - Pramestuti, Nova; Sianturi, Corry Laura Junita; Lestari, Eva; Wijayanti, Siwi Pratama Mars (Jurusan Kesehatan Masyarakat dan Fakultas Ilmu-Ilmu Kesehatan Universitas Jenderal Soedirman, 2019)
Reports on the rodenticide effect of papain papaya to control rats and mice is scarce. The aim of this study was to determine pathological changes in  albino mice internal organs (gaster, kidney, liver and intestine) associated with toxicity effect of papain papaya (Carica papaya L.). Seventy-eight adult BALB/c mice of both sexes were divided into 5 groups: 1 control group and 4 treatment groups that were given papain feeding block. Feed intake and mortalities have been monitored in previous study. At the end of the experimental period, tissues of mice were harvested for necropsy and histopathological examination. The abnormality of post mortem examination were hepatomegaly, gastro-intestinal bleeding. Dark discoloration was founded in liver and gaster. Histopathological changes founded in all treatment albino mice were necrosis in gaster, kidney, liver and intestine. Cloudy swelling occurred in liver and dilatation in kidney. Fatty degeneration occured in gaster, liver and intestine. In addition, the kidney and liver were congested. Feed intake of 16 to 32% papain natural rodenticide gave effect to the organs of studied mice, i.e gaster, kidney, liver and intestine.Reports on the rodenticide effect of papain papaya to control rats and mice is scarce. The aim of this study was to determine pathological changes in  albino mice internal organs (gaster, kidney, liver and intestine) associated with toxicity effect of papain papaya (Carica papaya L.). Seventy-eight adult BALB/c mice of both sexes were divided into 5 groups: 1 control group and 4 treatment groups that were given papain feeding block. Feed intake and mortalities have been monitored in previous study. At the end of the experimental period, tissues of mice were harvested for necropsy and histopathological examination. The abnormality of post mortem examination were hepatomegaly, gastro-intestinal bleeding. Dark discoloration was founded in liver and gaster. Histopathological changes founded in all treatment albino mice were necrosis in gaster, kidney, liver and intestine. Cloudy swelling occurred in liver and dilatation in kidney. Fatty degeneration occured in gaster, liver and intestine. In addition, the kidney and liver were congested. Feed intake of 16 to 32% papain natural rodenticide gave effect to the organs of studied mice, i.e gaster, kidney, liver and intestine.